A Study to Assess the Impact of Infertility on Marital and Sexual Satisfaction among Infertile Women Visiting Selected Infertility Clinics of City Ludhiana, Punjab - Harpreet Kaur; Nidhi Sagar; Mamta; Simranjeet Kaur (International Journal of Emergency and Trauma Nursing and Practices, 2023)
Infertility has been described as a stressor and a life crisis for infertile women, which results in a lower marital and sexual satisfaction. More dissatisfaction is felt by infertile women, and both direct and indirect negative effects on the marriage are brought on by stress connected to infertility and its treatment. Having social support from family, a partner, and friends can help infertile women cope with a variety of stressors in their lives. The purpose of this study is to evaluate how infertility affects infertile women’s marital and sexual pleasure. A study was conducted on 80 infertile women visiting selected clinics of city Ludhiana Punjab selected by convenience sampling technique. Marital satisfaction was assessed by using a Modified ENRICH Marital Satisfaction scale and Sexual Satisfaction was assessed by Modified Sexual Satisfaction Scale for Women (SSS-W). An analysis was done by using both descriptive and inferential statistics. The findings of the study revealed that (88.8%) infertile women were satisfied and (11.2%) infertile women were partially satisfied related to marital and sexual relationship, the mean score of marital satisfaction was 69.70 ± 7.299 and the mean score of sexual satisfaction was 80.54 ± 9.195. Also, it was discovered that some sociodemographic factors, such as age, education, and religion, had a statistically significant association with sexual satisfaction at the (p < 0.05) level. Significant association of sexual satisfaction among infertile women with maternal profile like number of abortions and failure of treatment were at the (p < 0.05) level. Thus, the study concluded that most of infertile women were satisfied related to marital and sexual relationship.
Keywords: Infertility; infertile women; marital satisfaction; sexual satisfaction